Pengaruh Motivasi Dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan Pada PT. Pegadaian (Persero) Kanwil I Medan - Rahmad Bahagia; Fahri Wanda Sinaga (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
The purpose of this study was to determine the effect of motivation and self-development on employee job satisfaction. The population in this study were all employees and the number of samples in this study was 70 people. Data collection techniques used are classical assumptions, multiple linear regression, f test, t test of the coefficient of determination. The results showed that there was a significant influence between motivation and job satisfaction. The existence shows that there is a significant influence between career development and job satisfaction. And motivation and career development simultaneously have a significant effect on job satisfaction at PT. Pegadaian (Persero) Regional Office 1 Medan